2012
DOI: 10.1097/cej.0b013e32834dbc81
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of the metabolic syndrome and risk of colorectal cancer in postmenopausal women

Abstract: The metabolic syndrome is associated with increased risk of diabetes and coronary heart disease. Although higher BMI and other related factors have been frequently associated with colorectal cancer (CRC), whether the metabolic syndrome is associated with the risk of colorectal cancer is unclear. We therefore assessed the association of the metabolic syndrome with the risk of CRC in a subsample of participants of the Women’s Health Initiative who had repeated measurements of the components of the syndrome at ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 46 publications
(87 reference statements)
5
27
0
Order By: Relevance
“…Kabat et al used WHI data to identify 81 incident cases of colorectal cancer among 4862 eligible women with median follow-up of 12 years, and found that among the individual components of metabolic syndrome, only elevated fasting glucose was associated with higher risk of colorectal and colon cancer (23), which is consistent with our findings. In other studies, elevated fasting glucose or diabetes has been repeatedly shown to be associated with the risk of colorectal and colon cancer (24, 25).…”
Section: Discussionsupporting
confidence: 88%
“…Kabat et al used WHI data to identify 81 incident cases of colorectal cancer among 4862 eligible women with median follow-up of 12 years, and found that among the individual components of metabolic syndrome, only elevated fasting glucose was associated with higher risk of colorectal and colon cancer (23), which is consistent with our findings. In other studies, elevated fasting glucose or diabetes has been repeatedly shown to be associated with the risk of colorectal and colon cancer (24, 25).…”
Section: Discussionsupporting
confidence: 88%
“…In term of MetS, previous studies also have reported that MetS was a risk factor for colorectal neoplasm. [12,17–19] Ahmed et al [20] investigated a large size of participants including 14,109 individuals and found that MetS had a positive association with incidence of CRC. [19] As there is a close association between NAFLD and the various component features of the MetS, including abdominal obesity, insulin resistance, dyslipidemia, and so on, NAFLD is often considered the hepatic manifestation of the MetS.…”
Section: Discussionmentioning
confidence: 99%
“…A remarkable body of epidemiologic data collected over the past 2 decades indicates that the risk of colon cancer is elevated and the prognosis of colon cancer is worse in subjects with MS. 68 The mechanism underlying these associations is unknown, but experimental and clinical investigations have indicated the possible involvement of various biological processes such as IGF-1R pathway, 20,21 VEGF pathway, 12 inflammation, 22,23 intratumoral immune modulation 16 and advanced glycation end-products and its receptors. 17 The novel approach of our study was to observe these potential mechanisms of action in an integrated manner to determine the most relevant targets that may be subsequently studied for therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…4 The MS and diabetes are known risk factors for colon cancer and these patients have a higher rate of relapse of their cancer as well. 68 Several potential mechanisms have been proposed. However, their relative contribution to outcome in humans has not been assessed.…”
Section: Introductionmentioning
confidence: 99%